Novel Energy Efficient Protocols for Gaussian & Uniform Distributed Heterogeneous Wireless Sensor Networks - Kumar, Vinay; Devi, Kuthadi Gayatri; Yadav, Sadanand; Sengupta, Joydeep; Dhok, S. B. (Discoveries in Agriculture and Food Sciences, 2016)
Network lifetime is a critical concern in the design of wireless sensor networks (WSNs). Prolonged network lifetime is desired characteristics of WSNs. Gaussian distributed heterogeneous WSNs can fulfill such requirement and are widely deployed in realistic scenarios. In addition, the presence of some heterogeneous sensor nodes leads to performance enhancement in terms of intrusion detection probability, network lifetime, end to end delay and throughput. In this paper, we have proposed novel routing-chains protocols for Gaussian and uniformly distributed heterogeneous sensor networks. Proposed protocols, lifetime enhancement in Gaussian distributed heterogeneous sensor network (GHetLESN) and lifetime enhancement in uniformly distributed heterogeneous sensor network (UHetLESN) have been compared with existing energy efficient chain formation (EECF) protocol. We have also presented the results that how much percentage of heterogeneity of total nodes will provide good impact on network lifetime. By experimentation, it is shown that proposed protocols GHetLESN provides 4.76 times improvement in network lifetime compare to existing protocol EECF and UHetLESN provides 1.78 time improvement in network lifetime compare to EECF.